Fronteira étnica : Tabajara e comunidades negras no processo de territorialização do litoral sul paraibano - Marques, Amanda Christinne Nascimento (2015)
This study aims at analyzing the territorialization process of the south coast of Paraíba microregion, more specifically, the ethnic territoriality of the Tabajara and the Black Communities in Gurugi and in Ipiranga. These groups, in different historical periods, have established territorial and interethnic relations which, at the same time, differentiate and approximate themselves.This research starts from some analytical issues, such as: in a conflict situation, by which it is being installed,what legal mechanisms, stakeholders, oligarchic families and conflicts are there in this territorial part? How do subaltern people use their silencing/speaking strategies to become visible? In what account is the ethnical mix favarable or unfavorable in the process of territorial vindication?To understand the dimensions of the identification process of indigenous and Quilombola groups, which are regarded as resistant and persistente groups, is required concepts such as territory, territoriality, and ethnicity in authors, as follow:Raffestin (1993), Moraes (1984), Souza (2003), Santos (1994), and Haesbaert (2002, 2004). It is intended to reconstruct historical situations in the south coast, through documents which reference the process of contact and ethnical territorialities (MARQUES, 2009), as exemples there are reports by presidents of the province, and documents of public lands colonizationin 1860. A bibliographical survey was proceeded in Higher Education Institutions (Instituições de Ensino Superior – IES), in addition to discussions on legislations and Laws which regulate and deal with the legal-political process of indigenous and Quilombolas lands, through reading the Brazilian Constitution, presidential decrees, agreements, and the Indian Statute. This investigation interpreted relations of power, historically established, among the groups and the State, as well as their way of living, by means of field work. This study considers the hypothesis that there are elements which maintains the subalternity in the Brazilian legislation, in demarcation processs, in representations of these groups, and in resistance practices.In that way, the ethnic territorial conflicts count on the State as a maintenance agent of subalternity relations among these groups.Most reasoning in this research is based on post colonial theories, in order to establish the Southern point of view, under the perspective of authors, such as: Said (2011), Spivak (2003;1994), Hall (2003;2006) and Bhabha (1998). Therefore, the ethnic groups located in the south coast claim, historically, to leave the condition of living in the in-betweeness.Getting out of the border-line condition means having their rights guaranteed in full.